CITRA HOTEL BERBINTANG DI DAERAH ISTIMEWA YOGYAKARTA - Sutomo, Maskuri (Jurusan Manajemen Fakultas Ekonomi dan Bisnis, 2011)
This study aims to describe identity and analyze reputation, socialresponsibility and physical environment of star hotels in Yogyakarta Province.Research methodology employed survey method. Respondent of this researchwere customers/guests of the three, four, and five star hotels in YogyakartaProvince. Result of the study shows that image of the three, four and five starhotel was influenced by their company’s identity, reputation, socialresponsibility, and physical environment. Among these factors, company’sidentity has dominantly influenced image of hotel. Marketing communicationthrough promotional mix is considered as main role in order to increaseresponds of customers toward company’s identity. Therefore, actualization ofmarketing communication performance must be good. Better promotionalmarketing management will develop understanding and respond of customersthat affect increasing of hotel’s image.